2015
DOI: 10.1139/apnm-2015-0391
|View full text |Cite
|
Sign up to set email alerts
|

Dietary HMB and β-alanine co-supplementation does not improve in situ muscle function in sedentary, aged male rats

Abstract: This study evaluated the effects of dietary β-hydroxy-β-methylbutyrate (HMB) combined with β-alanine (β-Ala) in sedentary, aged male rats. It has been suggested that dietary HMB or β-Ala supplementation may mitigate age-related declines in muscle strength and fatigue resistance. A total of 20 aged Sprague-Dawley rats were studied. At age 20 months, 10 rats were administered a control, purified diet and 10 rats were administered a purified diet supplemented with both HMB and β-Ala (HMB+β-Ala) for 8 weeks (appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…In the present study, pretreatment with HMB prevented muscle atrophy. Our data are consistent with those of previous studies, showing that HMB represses the expression of MuRF1 and atrogin-1 [ 8 10 ]. In a previous study, HMB did not repress the expression of MuRF1 and atrogin-1 and did not protect rats from skeletal muscle atrophy induced by monolateral hindlimb immobilization [ 49 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, pretreatment with HMB prevented muscle atrophy. Our data are consistent with those of previous studies, showing that HMB represses the expression of MuRF1 and atrogin-1 [ 8 10 ]. In a previous study, HMB did not repress the expression of MuRF1 and atrogin-1 and did not protect rats from skeletal muscle atrophy induced by monolateral hindlimb immobilization [ 49 ].…”
Section: Discussionsupporting
confidence: 94%
“…HMB also attenuated dexamethasone-induced muscle atrophy by regulating FOXO transcription factor and subsequent MuRF1 expression in rats [ 9 ]. In aged male rats, HMB reduced the expression of MuRF1 [ 10 ]. HMB has also been suggested to repress the expression of IL-6 [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased protein breakdown observed in the elderly receiving a supplement of Similarly, Russ et al (2015) showed recently that HMB treatment combined with β-alanine in sedentary aged male rats (20 months) reduces muscle MuRF1 expression as compared to control rats. Similar data have been obtained in muscle cell cultures exposed to wasting treatments such as TNF-α, IFN-, and GCs (dexamethasone) (Aversa et al, 2012;Giron et al, 2015;Kimura et al, 2014a).…”
Section: Hmb: a Very Potent Strategy Against Various Muscle-wasting Cmentioning
confidence: 94%
“…In contrast, meta-analysis of protein supplementation studies (Xu et al 2014 ) showed no difference between the effect of protein supplementation and that of a placebo groups on muscle mass, protein synthesis and muscle strength in older men (Dirks et al 2014 ) or women (Zhu et al 2015 ). Furthermore, (Russ et al 2015a , b ) showed that protein supplementation attenuated muscle degradation through decreasing Murf1 expression, this did not translate to any functional benefits to muscles of old rats (Russ et al 2015b ). However these discrepancies may be explained by the times at which intake of protein occurred; Symons et al ( 2007 ) showed that a 90 g of protein meal in humans does not cause more protein synthesis than a 30 g meal in humans (Symons et al 2007 ).…”
Section: Increase In Protein Intakementioning
confidence: 99%